2010
DOI: 10.1364/oe.18.007190
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigations on nonlinear dynamics in supercontinuum generation with feedback

Abstract: A system for supercontinuum generation by using a photonic crystal fiber within a synchronously pumped ring cavity is presented. The feedback led to an interaction of the generated supercontinuum with the following femtosecond laser pulses and thus to the formation of a nonlinear oscillator. The nonlinear dynamical behavior of this system was investigated experimentally and compared with numerical simulations. Steady state, period doubling and higher order multiplication of the repetition rate as well as limit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
12
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 27 publications
1
12
0
Order By: Relevance
“…The concept of GV matching has been used to show how the spectra can be extended into the deepblue by optimizing the fiber structure [3], by tapering the fiber [4][5][6], or by doping the fiber [7]. Other ways of pushing the spectrum toward the blue include seeding with the second harmonic [8], using concatenated fibers [9], or back-seeding part of the SC [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…The concept of GV matching has been used to show how the spectra can be extended into the deepblue by optimizing the fiber structure [3], by tapering the fiber [4][5][6], or by doping the fiber [7]. Other ways of pushing the spectrum toward the blue include seeding with the second harmonic [8], using concatenated fibers [9], or back-seeding part of the SC [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…For such lasers the pulse breakup is initiated by noise-driven modulational instability (MI), which causes large shot-to-shot fluctuations. It has been demonstrated that the noise can be significantly reduced by modulating the pump pulse in order to ensure a deterministic rather than noise-driven pulse breakup [3][4][5][6][7][8][9][10][11]. Seeding was numerically investigated in [5,6,10,11].…”
Section: Introductionmentioning
confidence: 99%
“…In all cases a phase coherent seed was used to achieve a coherent pulse break-up through the amplification of a cascade of four-wave mixing (FWM) side-bands. Experimentally, seeding was investigated in [3,4,[7][8][9]. In [3,8,9] the seed was used to trigger sub-threshold SC generation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, by adding an external seed light or by modulating the pump pulse envelopes [3][4][5]. A different approach is to utilize a feedback to influence the SC generation, where a fraction of the generated SC was used as a seed for the following pump pulse [6][7][8]. But until now, control of the SC generation and its properties still remains a big challenge.…”
mentioning
confidence: 99%